Electrospun Ternary Composite Metal Oxide Fibers as an Anode for Lithium-Ion Batteries - Ling, JinKiong; Karuppiah, Chelladurai; Das, Santanu; Misnon, Izan Izwan; Ab. Rahim, Mohd Hasbi; Yang, Chun-Chen; Jose, Rajan (Frontiers in Materials, 2022)
Nickel-cobalt-manganese oxide (NCM) had been widely applied as cathode materials given their beneficial synergistic effects of high storability, electrical conductivity and stability. However, studies on adopting similar materials for anode of lithium-ion batteries were lacking. Herein, a NCM nanofibers was prepared using multi-needle electrospinning techniques and testing as the anode for lithium-ion batteries. The NCM nanofibers demonstrated an initial discharge capacity of 1074.8 mAh/g with an initial capacity loss of 42%. Through manipulating the conductive additives content, the initial discharge capacity can be further improved to 1810.4 mAh/g, mostly attributing to the improved inter-fiber connectivity supported by the significant lowering of impedance when the amount of conductive additive is increased. This study also reveals that the conventional ratio of 80:10:10 wt% (active materials:additives:binder) is not optimal for all samples, especially the high active surface area electrospun nanofiber.